The rise of the Ku Klux Klan: right-wing movements and national politics - McVeigh, Rory (Social movements, protest, and contention, 2009)
The Klan as a national movement -- The rebirth of a Klan nation, 1915-1924 -- Power devaluation -- Responding to economic change : redefining markets along cultural lines -- National politics and mobilizing "100 percent American" voters -- Fights over schools and booze -- How to recruit a Klansman -- Klan activism across the country -- The Klan's last gasp : campaigning to keep a Catholic out of the White House, 1925-1928 -- Conclusion: Right-wing movements, yesterday and today